2019
DOI: 10.3892/ijo.2019.4876
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new cancer stem cell markers and signaling pathways in HER‑2‑positive breast cancer by transcriptome sequencing

Abstract: Human epidermal growth factor receptor (HER)-2-positive breast cancer accounts for ~25% of all breast cancer cases, has a high propensity for relapse, metastasis and drug resistance, and is associated with a poor prognosis. Therefore, it is necessary to develop more effective therapeutic targets for the treatment of HER-2-positive breast cancer. CD44+/CD24−/low is currently the most commonly used marker for breast cancer stem cells (CSCs), which are considered the main cause of drug resistance, relapse and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…Consistent with our results, all of these three signaling pathways had been reported to be markedly related to colon cancer [33][34][35]. As reported by previous articles, Wnt and ERBB signaling pathway played important roles in cancer [36,37]. Yan et al reported that LINC00261 could regulate miR-324-3p and the Wnt signaling pathway to repress colon cancer progression [38].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, all of these three signaling pathways had been reported to be markedly related to colon cancer [33][34][35]. As reported by previous articles, Wnt and ERBB signaling pathway played important roles in cancer [36,37]. Yan et al reported that LINC00261 could regulate miR-324-3p and the Wnt signaling pathway to repress colon cancer progression [38].…”
Section: Discussionsupporting
confidence: 91%
“…Surface markers, such as CD133 and CD90, are widely used to identify CSCs [ 23 , 25 , 27 ], but the expression of these surface markers was not observed in Hep3B/ρ 0 cells (data not shown). However, some studies suggest that the classification of CSCs using surface markers is not accurate [ 40 , 41 , 42 ]. Therefore, we focused on the acquisition of superior self-renewal capability in Hep3B/ρ 0 cells regardless of the presence of the markers.…”
Section: Discussionmentioning
confidence: 99%
“…The ALDH3B2 gene encodes a member of the aldehyde dehydrogenase family, a group of isozymes that play a role in the detoxification of aldehydes generated by alcohol metabolism and lipid peroxidation. Gene overexpression has been associated with breast cancer stem cells [ 52 ]. The ASPN gene encodes the Asporin protein, which is thought to regulate chondrogenesis by inhibiting transforming growth factor-beta 1-induced gene expression.…”
Section: Discussionmentioning
confidence: 99%